Fintech Integration with Crowdfunding and Blockchain in Industry 4.0 Era - Tasya Syafira; Stuart Jackson; Amirsyah Tambunan (Startupreneur Business Digital (SABDA Journal), 2024)
The Industrial Era 4.0 has brought significant changes in various sectors, including the financial sector. This research aims to examine in depth the integration of FinTech with Crowdfunding and Blockchain, as well as its implications in the context of the Industry 4.0 era. The method used in this research is qualitative analysis with a literature study and case study approach. The research results show that FinTech has played a catalyst role in accelerating the adoption of Crowdfunding and Blockchain. This integration has created a new business model that is more efficient, transparent and inclusive. In the context of Crowdfunding, FinTech has enabled wider access for individuals and small businesses to obtain funding, while in the context of Blockchain, FinTech has contributed to increased security, reduced transaction costs and increased trust. This research provides new insights into how the integration of FinTech with Crowdfunding and Blockchain can shape the future of financial services in the Industry 4.0 era   https://www.prima-school.com/menyelami-dunia-slot-gacor-strategi-dan-analisis-terbaru-dalam-perjudian-online/ https://www.schmeler.net/permainan-slot-online-terbaik-di-indonesia-menjelajahi-dunia-kasino-virtual/ https://lastnewsusa.com/panduan-lengkap-slot-gacor-membangun-strategi-untuk-memenangkan-permainan-kasino-online/ https://apside-clothes.com/menavigasi-dinamika-slot-online-perspektif-mendorong-inovasi-di-kasino-digital-indonesia/ https://dibsie.com/menemukan-slot-gacor-strategi-dan-panduan-terbaik-untuk-pemain-kasino-online-di-indonesia/ https://21stcenturyaffiliatemarketing.com/panduan-komprehensif-untuk-memahami-slot-online-di-kasino-digital-indonesia/ https://acedissertation.co.uk/slot-gacor-menyingkap-rahasia-permainan-mesin-slot-terbaik-di-kasino-online/ https://www.acheter-fichier-email-professionnel.com/menjelajahi-slot-online-panduan-lengkap-untuk-pemain-kasino-di-indonesia/ https://acheterupermisdeconduire.com/mengungkap-rahasia-slot-gacor-strategi-dan-pengalaman-bermain-di-kasino-online/ https://www.airjordan4premium.com/menelusuri-keberuntungan-strategi-dan-taktik-bermain-slot-di-kasino-online-indonesia/